Preaching as homecoming : a practical theological study of proclaiming belonging and identity in the South African Anglican context from 1990 to 2017 - Davis, Sharon (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.